Tapping panel dryness in Hevea brasiliensis: Investigations on the gene transcripts from latex by suppression subtractive hybridization - Mohamed Sathik, M.B.; Mary Jose, Rani; Kochunni, Deena T.; Musthapha, Mrudula P.; Thomas, Molly; Jacob, James (Journal of Plantation Crops, 2009)
-